2021
DOI: 10.1002/cplu.202100233
|View full text |Cite
|
Sign up to set email alerts
|

Illumination Intensity Dependence of the Recombination Mechanism in Mixed Perovskite Solar Cells

Abstract: Recombination mechanisms in solar cells are frequently assessed through the determination of ideality factors. In this work we report an abrupt change of the value of the “apparent” ideality factor (nAP) in high‐efficiency FA0.71MA0.29PbI2.9Br0.1 based mesoscopic perovskite solar cells as a function of light intensity. This change is manifested as a transition from a regime characterized by nAP∼1.8–2.5 at low light intensities (<10 mWcm‐2) to one characterized by nAP∼1. This transition is equally observed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 59 publications
0
19
0
Order By: Relevance
“…According to previous works, the change in the β parameter suggests a different main recombination mechanism inside of the PSC, although some ionic effects cannot be ruled out. [ 29,34 ] On the other hand, Figure S5, Supporting Information, shows that the high‐frequency capacitance is also not significantly altered by the presence of Adamantane interlayer.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous works, the change in the β parameter suggests a different main recombination mechanism inside of the PSC, although some ionic effects cannot be ruled out. [ 29,34 ] On the other hand, Figure S5, Supporting Information, shows that the high‐frequency capacitance is also not significantly altered by the presence of Adamantane interlayer.…”
Section: Resultsmentioning
confidence: 99%
“…For the sake of clarity, we differentiate this ideality factor from other solar cells, where it is just determined by electron dynamics. Hereafter, we will call “ m ” the apparent ideality factor of PSCs. ,, The ideality factor can be related to the recombination mechanism . Also, it has been recently used to track the performance of PSCs outdoors …”
Section: Resultsmentioning
confidence: 99%
“…Hereafter, we will call "m" the apparent ideality factor of PSCs. 40,48,49 The ideality factor can be related to the recombination mechanism. 50 Also, it has been recently used to track the performance of PSCs outdoors.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%
“…In recent work it has been shown that ionic features can also affect the recombination parameters and complicate the interpretation of the impedance spectrum and the ideality factor. 22,26,30,56 Recently, Bennett and coworkers 30 have proposed an “electronic” ideality factor which is not “contaminated” by the ionic properties of the sample. This quantity is calculated via where q is the elementary charge, R hf is the high frequency resistance described before and J rec the DC recombination current.…”
Section: Discussion and Modellingmentioning
confidence: 99%
“…Photovoltaic performance in PSC is also strongly dependent on recombination kinetics. Charge collection efficiencies are determined by the interplay between recombination in the bulk and at the interfaces [19][20][21][22] and the internal electric eld created by ion migration and ion accumulation at the interfaces. [23][24][25][26] Thus, electronic recombination and ion motion phenomena are linked to each other in PSC under operation.…”
Section: Introductionmentioning
confidence: 99%